Social Stances and (Unobtrusive) Resistance in Kaunas During the Late Soviet Period - Bulota, Rytis (Sociologija. Mintis ir veiksmas, 2011)
This article deals with the main oppositional stances and their manifestations in Kaunas during the late Soviet period, employing the theoretical model of ‘unobtrusive practices of contention’ as formulated by H. Johnston and C. Mueller. During the analysed period the main oppositional groups in occupied Lithuania were of a rather non-conformist nature. One of the socially recognisable and visible forms of ideological protest was represented by ethno-cultural and Catholic movements, based on traditional values, another, by prowestern subcultures or artists’ gatherings. Even though the activities of these groups allow us to comprehend them analytically as the main hotbeds of resistance, strong negative stances towards the Soviet regime were widespread in the rest of society. Such stances didn’t acquire the form of evident, declarable or socially visible practices, yet they contributed to the success of Sąjūdis as a social movement. Social movements are largely connected with a collective identity and the securing or preservation of it. The oppositional stances discussed in the article grounded such a collective identity. Its existence provides an explanation of the rapid mobilisation of the movement – in just three weeks after its establishment in the rallies of Sąjūdis tens of thousands and very soon afterwards hundreds of thousands participated.